Konsep Nilai Kemanusiaan di dalam Filsafat Jawa - Parmono, R. (Jurnal Filsafat "WISDOM", 1999)
In his life, a human has got the process of change for being himself if better than those before hand. A human is enhistorying creature and making history. Hence, in his life will satisfied, if his activity consist of a believable truthful value. The value as the quality of life, encourages, directs his activity, so the overhelms to make himself as a person of value in his life. The probelm in that though there are many studies having been done about the value of humanity, in the other hand, they are still too many of them influenced by system of the West Philosophy. In case of digging Indonesia philosophy (especially Javanese one), there is still a gap in understanding about value of humanity.The term of kind himself, introduces to the following probelm that human have not fully understood themselves. Human do their life in a process of 'becoming', while they themselves include in the process of change. Where the process going to go? Whom human interact in the process of change. Where process going? What values will be reached in this process?In this Javanese cultural treasure, philosophy is not only meant just a knowledge about life skillfulness, but an effort to reach the complete life happiness. Thus, the value of humanity according to Javanese philosophy, is the attitude and activity to always being interrelationship in the balanced position; so it makes the tendency in life to anticipate the future time with a set of values and norms, in order it become better than beforehand.Based on the exiting data is, held a methodical reflection for attaining the synthesis in new understanding about the major thoh about special Javanese humanity values. This activity is afforded as pure as possible, so it can be attained the substance and dynamic; as the more concrete desciption intact and originla. Where as the crystallization in the form of sturggle to make thmenselves better life a natural (human) struggle, in the ambition to got into the Super Power being, as the ideal human image. This understanding will give some positive thought, for developing complate Indonesia people and qualified increasing human resource. The concept of human value in Javanese philosophy, having harmonious unique multiple dimension, as an intact and comprehensive intergrated unityÂ